Unilateral pulmonary miliary tuberculosis with abdominal tubercular lymphadenitis in an apparently immunocompetent adult: A case report - Amit Toshniwal; Sumer Chaudhary; Varun H; Babaji Ghewade; Alushika Jain (IDCases)
Atypical forms of tuberculosis (TB) are gaining recognition, challenging traditional diagnostic criteria classically linked to chronic cough, lethargy, anorexia, evening pyrexia, and weight loss in immunocompromised patients. We present the case of a 23-year-old immunocompetent man from rural central India who developed unilateral pulmonary miliary TB with concurrent abdominal TB lymphadenitis. The patient presented with a two-month history of chronic cough and diffuse abdominal pain. Initial chest radiograph revealed unilateral, right-sided miliary opacities, while abdominal ultrasonography indicated mild circumferential bowel wall thickening and enlarged mesenteric lymph nodes. High-resolution computed tomography (HRCT) of the thorax showed multiple tiny centrilobular and peri-bronchovascular hyperdense nodules in the right lung, and contrast-enhanced computed tomography (CECT) of the abdomen confirmed necrotic mesenteric and para-aortic lymph nodes. Sputum microscopy was negative for acid-fast bacilli (AFB), but bronchoalveolar lavage (BAL) tested positive for AFB, and Truenat MTB PCR confirmed Mycobacterium tuberculosis (MTB) with a load of 6.3 × 10^2 CFU/mL. The patient was diagnosed with unilateral pulmonary miliary TB with abdominal TB lymphadenitis and was treated under the WHO Category I Directly Observed Treatment, Short-course (CAT 1 DOTS) regimen (2HRZE/4HRE) under the National Tuberculosis Elimination Program (NTEP). Symptomatic improvement was observed within four weeks, and a six-month follow-up confirmed clinical and radiological resolution. Despite India’s high TB burden, unilateral miliary lung involvement with abdominal lymphadenitis remains rarely reported in immunocompetent hosts. This report emphasises the need for heightened clinical vigilance to optimise detection and management, contributing to global TB elimination efforts.